2007
DOI: 10.1063/1.2434168
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle generation in ultrafast pulsed laser ablation of nickel

Abstract: The process of particle generation during ultrafast pulsed laser ablation of nickel is investigated. Two types of particles with different sizes depending on the laser fluence are found, indicating different particle generation mechanisms. By limiting the laser fluence below a threshold of strong plasma formation, the large dropletlike particles can be eliminated. In addition, by supplying different background gases, various crystalline structures are obtained for the particles, including Ni∕NiO core/shell sph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(52 citation statements)
references
References 21 publications
2
48
0
2
Order By: Relevance
“…Compared to conventional manufacturing routes, methods of fabrication of nanoparticles using laser ablation in liquids promise much higher material purity, since no chemical precursors are required. [1][2][3][4][5] The nanoparticle generation is carried out by ablation in a liquid transparent for near-infrared radiation ͑such as water, ethanol, acetone, etc.͒ so that an in situ dispersion of nanoparticles in organic solvents become possible. 2,5 When ultrashort laser pulses are applied instead of nanosecond laser pulses, the stoichiometry ͑e.g., of nanoparticle alloys͒ is less altered during the conversion of the bulk material ͑alloy͒ into nanoparticles.…”
Section: Generation Of Nanoparticle Colloids By Picosecond and Femtosmentioning
confidence: 99%
“…Compared to conventional manufacturing routes, methods of fabrication of nanoparticles using laser ablation in liquids promise much higher material purity, since no chemical precursors are required. [1][2][3][4][5] The nanoparticle generation is carried out by ablation in a liquid transparent for near-infrared radiation ͑such as water, ethanol, acetone, etc.͒ so that an in situ dispersion of nanoparticles in organic solvents become possible. 2,5 When ultrashort laser pulses are applied instead of nanosecond laser pulses, the stoichiometry ͑e.g., of nanoparticle alloys͒ is less altered during the conversion of the bulk material ͑alloy͒ into nanoparticles.…”
Section: Generation Of Nanoparticle Colloids By Picosecond and Femtosmentioning
confidence: 99%
“…Ausanio et al 28 and Amoruso et al 30 also reported the synthesis, structure, morphology, and magnetic characterization of Ni and Fe nanoparticles or, as they call them, nanocrystal films. Very recently, Liu et al 29 reported also on the generation of Ni nanoparticles by ultrafast PLD, but no magnetic characterization was included. In addition, the influence of surface-plasmon resonances in the magneto-optical ͑magne-toplasmonic͒ activity of noble-metal/ferromagnet/noblemetal continuous films and nanodiscs has recently been highlighted, [32][33][34][35] and there is a growing interest in exploring similar phenomena in systems fabricated using innovative methods.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, several groups have recently started to study the deposition and physical properties of nanoparticles obtained by fs-PLD from a variety of targets, such as Ge, 22 Permalloy, 23 Si, 24,25 Ti, 26 Al, 27 Ni, 28,29 or Fe. 30 The common feature is that different materials seem to behave roughly the same when irradiated with intensities around the threshold of plasma formation, typically 10 12 -10 13 W / cm 2 , leading to nanoparticle formation, with radii of tens of nm.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, nanoripples (Hsu et al, 2007;Luo et al, 2008;Sakabe et al, 2009;Jia et al, 2010;Yang et al, 2010;Bonse & Krüger, 2010;Okamuro et al, 2010;Huang et al, 2009), nanoparticles (Jia et al, 2006;Luo et al, 2008;Teng et al, 2010), nanocones (Nayak et al, 2008), and nanospikes (Zhao et al, 2007b) have been induced in various materials using single-beam fs laser pulses in air. In addition, fs laser ablation for metals and semiconductors in a vacuum environment (Amoruso et al, 2004;Liu et al, 2007a) and in liquid (Tsuji et al, 2003) have also been extensively investigated. These results are a strong indicator of the application potential of fs laser pulses in science and industry.…”
Section: Introductionmentioning
confidence: 99%